Royalism and the crisis of elite governance in Thailand (2016)
In May 2014, the Royal Thai Armed Forces launched a coup to establish a junta called the National Council for Peace and Order. In this interview, Social Transformations editor Lisandro Claudio (LC) speaks to historian Thongchai Winichakul (TW) of the University of Wisconsin, Madison, and Political Scientist Pavin Chachavalpongpun (PC) of Kyoto University to examine the simmering tensions the undergrid military take over.
Keywords: Thongchai Winichakul -- Interviews; Pavin Chachavalpongpun -- Interviews; Thailand -- Politics and government